ROLE OF GANDHAK RASAYAN IN SHUSHKA VICHARCHIKA (ECZEMA) (AYUSHDHARA, 2017)
In Ayurveda context, eleven types Kshudrakushtha are described and Vicharchika (Eczema) is one of them. In ancient text, there described many lines of treatmentsof Vicharchika (Eczema) like leech application, local application and many oral medicines. Gandhak Rasayanais one of the oral medicines described for many skin diseases.For this study, 30 patients of Shushka vicharchika (Dry Eczema)having complaint of Kandu, Daha, Ruja, Sparshaasahatva, Tvakvaivarnya were selected.Vicharchika (Eczema)is Kaphajavyadhi and Raktadushti is also observed. Gandhak Rasayana (Bharat Bhaishajya Ratnakar 1153) mainly acts on skin, blood and it is Rasayana in action. So it more or less acts on all Doshas and Dhatus. Gandhak isushnaveeryatmaka and Katu rasa Vipaki so acts as best Kaphghna and Kledaghna. During making of Gandhak Rasayana different twelve Drawyabhavanas are given to Shudhagandhak. These drugs helps to destroy the Samprapti of Vichrchika due to its Ushnavirya and Katukashay rasa. Some Bhavanadravyas has property of Madhur rasa, Sheet Virya due to which they acts as Pittaghna and Raktaprasadana and helps to cure Vicharchika (Eczema).Daha, Kandu, Ruja and Sparshaasahatva were significantly reduced. Also significant relief in Tvak-vaivarnyata was observed.